Kontribusi Perhatian Orangtua Dan Kebiasaan Belajar Terhadap Hasil Belajar Siswa Pada Bidang Studi Akidah Akhlak di MTs Mardiyah Islamiyah Panyabungan Kabupaten Mandailing Natal - Yusuf Hamidi; Muhammad Nuddin (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas Gunung Tua, 2024)
This study aims to determine the influence of parental attention and study habits on students' learning outcomes in the subject of Akidah Akhlak at MTs. Mardiyah Islamiyah in Panyabungan, Mandailing Natal. The research population consists of 262 seventh and eighth-grade students, and a sample of 66 students was selected using cluster sampling techniques. Data collection was carried out through questionnaires distributed to 66 respondents and documentation of students' learning outcomes in morality, which were then analyzed using statistical tools. The analysis results show that parental attention has a positive relationship with students' learning outcomes, with a correlation test result of 0.458 > 0.3173 (Rhit) and a t-value of 16.943 compared to a t-table value of 1.66940 at a 1% significance level. The higher the parental attention, the higher the students' learning outcomes, with a regression equation of Y = 40.813 + 0.614X and a contribution of 20.9%. Study habits also have a positive relationship with students' learning outcomes, based on a correlation test result of 0.562 > 0.3173 (Rhit) and a t-value of 5.431 compared to a t-table value of 3.14 at a 1% significance level. The higher the study habits, the higher the students' learning outcomes, with a regression equation of Y = 25.432 + 0.624X and a contribution of 31.5%.